Investigating Australian Male Expatriate, Longer‐Term and Frequent Traveller Social Networks in Thailand to Determine Their Potential to Influence HIV and Other STI Risk Behaviour - Crawford, Gemma (Curtin University, 2019)
Over the last decade, HIV infections have increased in Western Australia amongst Australian men travelling, living and working in Thailand. Using symbolic interaction as the theoretical lens, in-depth interviews, analysis of online forum posts and observational fieldwork led to a grounded theory explaining: 1) social network processes of male expatriates, longer-term or frequent travellers (ELoFTs); and 2) how ELoFT social networks may be harnessed for public health intervention, particularly via peer education and social influence.